2017
DOI: 10.1038/s41598-017-03768-9
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the DNA-binding domain of Myelin-gene Regulatory Factor

Abstract: Myelin-gene Regulatory Factor (MyRF) is one of the master transcription factors controlling myelin formation and development in oligodendrocytes which is crucial for the powerful brain functions. The N-terminal of MyRF, which contains a proline-rich region and a DNA binding domain (DBD), is auto-cleaved from the ER membrane, and then enters the nucleus to participate in transcription regulation of the myelin genes. Here we report the crystal structure of MyRF DBD. It shows an Ig-fold like architecture which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…For the control set, we were able to detect the N-terminal fragments of Flag-Myrf, Myc-Myrf, and HA-Myrf in the MB fraction ( Fig. 5D), consistent with its homo-trimerization 21,24,25 . The specificity of the second Myc immunoprecipitation step was confirmed by the lack of immunoblot signals in the MB fraction for the Set 3 samples.…”
Section: Scientific Reports |supporting
confidence: 57%
“…For the control set, we were able to detect the N-terminal fragments of Flag-Myrf, Myc-Myrf, and HA-Myrf in the MB fraction ( Fig. 5D), consistent with its homo-trimerization 21,24,25 . The specificity of the second Myc immunoprecipitation step was confirmed by the lack of immunoblot signals in the MB fraction for the Set 3 samples.…”
Section: Scientific Reports |supporting
confidence: 57%
“…In contrast, the nuclear entry step seems to be under regulation for the worm and slime mold orthologs of Myrf 4 , 8 , 9 . A recent structural study confirmed the homo-trimerization status for Myrf N-terminal fragments 16 , and we found that homo-trimerization imparts DNA-binding specificity to Myrf N-terminal fragment 15 , which provides a rational explanation for the lethal phenotype of the let-25 allele of C . elegans 8 .…”
Section: Introductionsupporting
confidence: 78%
“…First, in this study, we examined only SNPs located within the NOS2 gene region. Early research has shown that regions 20 kb up- and downstream of genes might contain some important regulatory elements and that variants within these regions could significantly affect gene expression levels [ 26 28 ]. Given of the limitations of single SNP analyses [ 29 35 ], for future replication studies, it is necessary to conduct haplotype analyses to provide further statistical evidence for our findings, and it is also important to consider those regions and investigate their potential contributions to the risk of non-union in the fracture healing process thoroughly.…”
Section: Discussionmentioning
confidence: 99%